2019
DOI: 10.1063/1.5099235
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic model of dispersive multi-step polarization switching in ferroelectrics due to spatial electric field distribution

Abstract: A stochastic model for polarization switching in tetragonal ferroelectric ceramics is introduced, which includes sequential 90 • -and parallel 180 • -switching processes and accounts for the dispersion of characteristic switching times due to a nonuniform spatial distribution of the applied field. It presents merging of the recent multistep stochastic mechanism (MSM) with the earlier nucleation limited switching (NLS) and inhomogeneous field mechanism (IFM) models. The new model provides a much better descript… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Particularly, the analysis revealed a substantial contribution of the fast processes, which do not cause macroscopic spontaneous strain and exhibit characteristics of non-180° switching events. Such coherent non-180° switching processes were indirectly identified in previous studies [34,37,38] and recently directly observed optically [64]. This is in agreement with a general conclusion from molecular dynamics that 180°-switching in tetragonal ceramics proceeds rather via sequential 90°-domain wall motion [25].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Particularly, the analysis revealed a substantial contribution of the fast processes, which do not cause macroscopic spontaneous strain and exhibit characteristics of non-180° switching events. Such coherent non-180° switching processes were indirectly identified in previous studies [34,37,38] and recently directly observed optically [64]. This is in agreement with a general conclusion from molecular dynamics that 180°-switching in tetragonal ceramics proceeds rather via sequential 90°-domain wall motion [25].…”
Section: Discussionsupporting
confidence: 89%
“…reflects the scaling properties of the polarization response observed on various bulk polycrystalline ferroelectrics [8,9,10,[34][35][36][37].…”
Section: Consecutive Switching Events In Polycrystalline Materials: a Hybrid Multistepinhomogeneous Field Mechanism (Msm-ifm) Modelmentioning
confidence: 83%
See 2 more Smart Citations
“…In that study, they observed different switching regimes in the dynamics during polarization reversal, which lead to name such type of switching as multiswitching states. [25,26] To understand the polarization reversal behavior with increase in [111] miscut angle, the evolution of polarization reversal with different magnitude of write voltage in different PZT crystal directions is carried out as shown in Figure 4a,b, and also in Figures S11-S22 in the Supporting Information. Figure 4a shows the VPFM phase scans for different switching voltages on the [416]/[111] 29.27° starting from the pristine state.…”
Section: Resultsmentioning
confidence: 99%